The Effects of Family Atmosphere, School Environment, and Self-efficacy on the Learning Outcomes of International High School Students with Different Levels of Anxiety in Learning English as a Second Language - Zhou, Yutong (Transactions on Social Science, Education and Humanities Research, 2024)
With the increasing number of students studying abroad and the majority of them choosing countries where English is the primary language, the anxiety of international school students learning English as a second foreign language (ESL) has drawn attention. Based on the factors that affect anxiety mentioned in most articles, this paper selects family atmosphere, school environment and self-efficacy as three studied factors, and makes chart analysis of the views of students with different anxiety states on the above three factors. The study found that people with low anxiety have higher English standardized scores than those with moderate and high anxiety. Parents' English level has some influences on their kids’ English performances, but whether they communicate with their kids using English in daily life has little influence on English learning. Also, there is no significant difference in whether the help provided by the school was beneficial for different anxious students. Finally, students with moderate anxiety have the highest sense of self-efficacy, even higher than students with highest anxiety. This study helps individual international students deeply understand the relationship between anxiety and ESL performance and the role of parents and schools, which can help teachers, parents and schools make better teaching methods.